Estupro no Brasil: Vítimas, autores, fatores situacionais e evoluç\~ao das notificaç\~oes no sistema de saúde entre 2011 e 2014 - Daniel Cerqueira; Danilo Santa Cruz Coelho; Helder Ferreira de Mendonça (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– In this article, the rape notifications registered in Brazil between 2011 and 2014 were analyzed based on data from the Notifiable Conditions Information System (Sinan) of the Ministry of Health. The phenomenon was also characterized according to these administrative records. More specifically, the profiles of victims and perpetrators were described, along with the relationship between them and other situational elements. An unacceptable unchanging statistical pattern over the period analyzed was noted, in which 69.9% of victims were children and teenagers, and over 10% of victims had physical and/or mental disabilities. In parallel, there was an increase in the proportion of gang rape cases, which in 2014 accounted for 15.8% of all cases, where in 25.6% the victim did not know the perpetrators. Another alarming finding was that 40.0% of child rapists were close family members, including the father, stepfather, uncle, brother and grandfather. The data draws attention to the seriousness of the problem of gender violence in Brazil and highlights the need to produce more accurate information allowing mitigating public policies to be devised that involve several State agencies, particularly in the educational field.
Keywords: I1; K14; 330; rape; Brazil; violence; Sinan; gender